Challenging the Environmental History of the Cerrado: Science, Biodiversity and Politics on the Brazilian Agricultural Frontier - Dutra e Silva, Sandro (Historia Ambiental Latinoamericana y Caribeña (HALAC) revista de la Solcha, 2020)
This article presents an overview of the environmental history of the Brazilian Cerrado, its environmental characteristics and the processes related to the historical change in the landscapes of this endangered ecosystem. It highlights competing classifications of the Cerrado, the role of politics in establishing them, and the environmental consequences of such classifications. More than just describing an environment, classifying an ecosystem is a political process that involves complex socio-environmental interactions. The sources used points out the different attempts to get to know and "conquered" the Cerrado, bringing together interdisciplinary perspectives from a variety of actors and institutions. Historiographic challenges go beyond environmental descriptions in that the socio-environmental interactions that made up this unique ecosystem are equally complex. This paper’s conclusions reinforce the interdisciplinary role of environmental history in the study of ecosystems and the complex relationship between culture and nature.